Clinical ethics and the necessity of stories essays in honor of Richard M. Zaner - Wiggins, Osborne P.; Allen, Annette C.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This collection of articles honors the work of Richard Zaner, a distinguished philosopher who has worked for over twenty years as an ethics consultant at Vanderbilt University Medical Center. His work in the clinical setting, especially the use of narrative in understanding what is going on in this setting, is the focus of some of the papers. Others relate his methodology and phenomenological approach to the more standard bioethical problems and approaches. The essential questions: What is the role of the phenomenological philosopher turned medical ethicist? Is medical ethics a form of applied philosophy, or is it also a form of therapy? What kind of ?ethics? emerges from a careful narrative rendering of clinical situations?
Clinical Ethics and the Necessity of Stories Osborne P. Wiggins and Annette C. Allen, editors TABLE OF CONTENTS 1. Osborne P. Wiggins and Annette C. Allen, "Introduction. 2. Rita Charon, "The Ecstatic Witness" 3. Arthur W. Frank, "The Philosopher as Ethicist, the Ethicist as Storyteller" 4. Paul A. Komesaroff, "Fardels of the Heart: Obesity and the Unbearable Heaviness of Being" 5. Hillel Braude, "Between and Beyond: Medicine and Narrative in Dick Zaner?s Phenomenology" 6. Stephen Hanson, "Richard Zaner and ?Standard? Medical Ethics" 7. Denise M. Dudzinski, "Integrity and the Moral Gestalt: Zaner Tells his Mother?s Story" 8. Robert Hunt Sprinkle, "Bioethics without Analogy" 9. John R. Scudder, Jr. and Anne H. Bishop, "Zaner?s Generative Spirit" 10. Thomas Nenon, "The Limits of Biomedical Ethics and the Specific Role of Phenomenology in Biomedical Ethics" 11. Lester E. Embree, "Phenomenological Nursing in Schutzian Perspective 12. Ronald R. Cox, "Richard Zaner on Transcendentality, Eidos and Phantasy" 13. Paul J. Ford, "A Story Teller?s Story: Richard Zaner as Hero (HE row) 14. Richard M. Zaner, "On the Telling of Stories".
Electronic reproduction.
Keywords: Zaner, Richard M; Medical ethics; Clinical medicine -- Moral and ethical aspects; Narration (Rhetoric) -- Psychological aspects; Physician and patient; Ethics, Clinical -- Festschrift; Narration -- Festschrift; Electronic books